The global negotiator : making, managing, and mending deals around the world in the twenty-first century / Jeswald W Salacuse - Salacuse, Jeswald W.
"The Global Negotiator provides managers, lawyers, executives, and government officials with a comprehensive guide to handling all kinds of negotiations from start to finish in the new era of global business. Jeswald Salacuse explains how to develop strategies for closing profitable deals from Bogota to Beijing, how to maintain them to your advantage once the contract is signed, and how to save them when they are threatened by conflict with foreign partners or hostile action by governments. Salacuse illustrates each of his principles and techniques with numerous real-life examples from every area of business. Being a global negotiator means not only that you are able to negotiate deals around the world, but also that you have the skills to handle the entire transaction from start to finish. The Global Negotiator guides you throughout the whole life of the deal, from the first handshake with a potential foreign partner to the final liquidation of a joint venture you no longer need."--Jacket